Motivation to paying Zakat: The role of religiosity, Zakat literacy, and government regulations - Muhammad Syauqi; Muslich Anshori; Imron Mawardi (Universitas Negeri Surabaya, 2022)
Zakat as an instrument of poverty alleviation, is considered very effective in distributing welfare. However, the reported zakat receipts in Indonesia are still far from the estimated revenue potential. This research examined the factors that motivate the payment of zakat through an official national institution or organization. This quantitative research employed the explanatory method, with data analysis techniques comprising the partial test (t), stimulant test (F), and the coefficient of determination (R2). Subsequently, the results indicated that the factors of religiosity, zakat literacy and government regulations simultaneously affect the motivation to pay zakat through a management agency. Partially influencing factors were zakat literacy and government regulations, while religiosity had no effect.